Analysis of Service Quality of the Sorong Regency Government Website using the WebQual 4.0 Method - Yusup Lukas Komiter; Indri Anugrah Ramadhan; Muhammad Ali Kasri (Universitas Islam Indragiri, 2026)
The rapid development of information technology has encouraged local government to adopt websites as platforms for delivering public information and services. This study aims to analyze the service quality of the Sorong Regency Government website based on user perceptions using the WebQual 4.0 method, which consists of three dimensions: usability, information quality, and service interaction quality. This study adopts a quantitative approach, with data collected through an online questionnaire administered to 49 respondents. The data were analyzed using SPSS, including validity and reliability tests and descriptive statistics. The results show that all 18 questionnaire items are valid and reliable, with a Cronbach’s Alpha value of 0.763. The mean scores for each dimension are 3.43 for usability (agree), 3.39 for information quality (somewhat agree), and 3.37 for service interaction quality (somewhat agree). These findings indicate that the overall service quality of the Sorong Regency Government website ranges from moderate to good, with usability identified as the strongest dimension. The novelty of this study lies in its focus on evaluating a local government website in a developing regional context, providing user-based evidence on WebQual 4.0 dimensions that remain underexplored in similar settings. This study provides empirical evidence that can support efforts to improve the quality of digital public services in Sorong Regency.